Digital addiction and the adolescent social interaction crisis: Integrating social displacement theory and Islamic ethics - Indriani Safitri (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The post-pandemic surge in digital usage has fundamentally altered adolescent social interaction patterns, characterized by declining interpersonal skills and weakened self-control. This study analyzes the adolescent social interaction crisis by integrating Social Displacement theory with an Islamic psychospiritual framework. Methods: This research employs an integrative literature review with thematic analysis. The analysis links the displacement mechanism, the shift of energy toward digital activities, with the Islamic psychological structure, specifically the dynamics between nafs al-ammarah, al-qalb, and al-’aql. Findings: Compulsive digital intensity triggers social displacement and signifies a collapse of internal regulation. The dominance of nafs al-ammarah undermines the rational function of al-’aql, leading to israf (excessiveness) and ghaflah (heedlessness) that degrade empathy and relationship quality. The principle of wasathiyyah is deemed insufficient if viewed merely as outward moderation, as digital challenges are inherently cognitive and internal. Conclusion: This study proposes tazkiyatun nafs and riyadah al-nafs (through practices ranging from muraqabah to tajalli) as a self-regulation recovery framework. While this model shows potential in mitigating digital addiction, further empirical validation is required. Novelty/Originality of this article: This study offers an integrative approach combining Social Displacement with Islamic psychospiritual dynamics to comprehensively explain the adolescent social crisis.